Oxidized Low-density Lipoproteins and Lipopolysaccharides Augment Carotid Artery Plaque Vulnerability in Hypercholesterolemic Microswine - Nooti, Sunil; Rai, Vikrant; Radwan, Mohamed M; Thankam, Finosh G; Singh, Harbinder; Chatzizisis, Yiannis S; Agrawal, Devendra K (Cardiology and Cardiovascular Medicine, 2023)
Atherosclerosis is a chronic inflammatory disease and hypercholesterolemia is a risk factor. This study aims to compare the potency of lipopolysaccharide (LPS) and oxidized low-density lipoproteins (oxLDL) to induce plaque formation and increase plaque vulnerability in the carotid artery of hypercholesterolemic Yucatan microswine. Atherosclerotic lesions at the common carotid artery junction and ascending pharyngeal artery were induced in hypercholesterolemic Yucatan microswine at 5-6 months of age with balloon angioplasty. LPS or oxLDL were administered intraluminally at the site of injury after occluding the arterial flow temporarily. Pre-intervention ultrasound (US), angiography, and optical coherence tomography (OCT) were done at baseline and just before euthanasia to assess post-op parameters. The images from the US, OCT, and angiography in the LPS and the oxLDLtreated group showed increased plaque formation with features suggestive of unstable plaque, including necrotic core, thin fibrous caps, and a signal poor region more with oxLDL compared to LPS. Histomorphology of the carotid artery tissue near the injury corroborated the presence of severe lesions in both LPS and oxLDL-treated pigs but more in the oxLDL group. Vascular smooth muscle and endothelial cells treated with LPS and oxLDL showed increased folds changes in mRNA transcripts of the biomarkers of inflammation and plaque vulnerability compared to untreated cells. Collectively, the results suggest that angioplasty-mediated intimal injury of the carotid arteries in atherosclerotic swine with local administration of LPS or ox-LDL induces vulnerable plaques compared to angioplasty alone and oxLDL is relatively more potent than LPS in inducing vulnerable plaque.